ANALISIS EFISIENSI KINERJA KEUANGAN OPZ DALAM MENGELOLA DANA ZIS DI INDONESIA: PENDEKATAN DATA ENVELOPMENT ANALYSIS - Apriyanto, Rizky; Muhammad Dandy Alif Wildana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to analyze the efficiency of the financial performance of Zakat Management Organizations (ZMOs) in Indonesia in managing Zakat, Infaq, and Sadaqah (ZIS) funds and analyzing cost efficiency and the potential for optimizing the collection and distribution of ZIS funds. This quantitative research uses a non-parametric approach with secondary data in the form of financial reports from several OPZ for the period 2018-2022. This research uses the Data Envelopment Analysis (DEA) method, output-oriented, and assumes the VRS model using MaxDEA lite 12.0.8 software. Input variables include personnel costs, socialization costs, operational costs, and total assets. Output variables include the receipt of ZIS funds and the distribution of ZIS funds. The analysis showed that out of 20 Decision Making Units (DMUs), seven DMUs had efficiency of less than 100%. Meanwhile, thirteen other DMUs reached 100% efficiency, namely BAZNAS from 2020 to 2022, LAZNAS Rumah Zakat Indonesia (RZI) from 2018 to 2022, LAZNAS Yayasan PPPA Daarul Qur'an and LAZNAS Dewan Dakwah Islamiyah Indonesia (DDII) in certain years. Inefficiency in ZMOs is caused by personnel costs, socialization costs, and total assets. These costs affect the optimization of OPZ resources in producing maximum output.